REFLECTION OF GENDER LINGUISTICS IN WOMEN'S SPEECH - Jo'rayeva Zuxroxon Yo'lchi qizi (Web of Journals Publishing, 2024)
This article talks about women's speech and its pragmatic realization, which is considered a unique basis of gender linguistics. It should be noted that women's speech differs from men's speech in terms of the inclusion of certain qualities, and this was analyzed as the object of this article.
Keywords: women's speech, pragmatic feature, speech behavior, genderology.